Gender Equality and Women's Empowerment Between Expectations and Reality in Small Cities - Cahyani, Cahyani; Anez, Celbi; Billa, Putri Salsa; Siswoyo, Mukarto; Khumayah, Siti (Green Publisher Indonesia, 2024)
One of the successes of development is that the role of men and women is very influential on the success of development. In this case, the Cirebon City government issued Regional Regulation Number 7 of 2021 concerning the Regional Medium Term Government Plan, namely